The Use of Fine-Needle Aspiration (FNA) Cytology in Patients with Thyroid Nodules in Asia: A Brief Overview of Studies from the Working Group of Asian Thyroid FNA Cytology - Chan Kwon Jung; SoonWon Hong; Andrey Bychkov; Kennichi Kakudo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Ultrasound-guided fine-needle aspiration (FNA) cytology is the most widely used screening and diagnostic method for thyroid nodules. Although Western guidelines for managing thyroid nodules and the Bethesda System for Reporting Thyroid Cytopathology are widely available throughout Asia, the clinical practices in Asia vary from those of Western countries. Accordingly, the Working Group of Asian Thyroid FNA Cytology encouraged group members to publish their works jointly with the same topic. The articles in this special issue focused on the history of thyroid FNA, FNA performers and interpreters, training programs of cytopathologists and cytotechnicians, staining methods, the reporting system of thyroid FNA, quality assurance programs, ancillary testing, and literature review of their own country's products. Herein, we provide a brief overview of thyroid FNA practices in China, India, Japan, Korea, the Philippines, Taiwan, and Thailand.